Hydrogel-based MPI Phantoms (Transactions on Additive Manufacturing Meets Medicine, 2025)
The validation and performance comparison of imaging modalities, particularly magnetic particle imaging (MPI), requires standardized procedures and phantoms. A challenge for MPI phantoms is the incorporation of structures smaller than 1 mm to demonstrate the high-resolution capabilities, while excluding magnetic or electrically conductive materials. A hydrogel-based phantom is presented, specifically designed for evaluating an in-house developed MPI scanner. Conventional phantom production methods typically involve hollow bodies filled with a magnetic nanoparticle (MNP) solution. As an extension, additive manufacturing enables precise geometric realization by printing phantoms as hollow bodies, allowing for flexibility in intricate structures. An alternative option is the direct 3D printing of phantoms by integrating the MNPs into the print material. Here, a resolution phantom is presented that has been directly manufactured via semi-solid extrusion, utilizing a suspension of MNPs in a hydrogel. In this initial experiment, a self-sealing phantom holder incorporating a circular print bed with a diameter of 29 mm was developed for integration with a bioprinter and hydrogel used. The imageable ink suspension was synthesized by combining the hydrogel, with ~110 mg of MNPs. The phantom was designed with four lines converging from the center at uniform 24° angular spacing, originating at a radius of 4.1 mm, extending 7.3 mm in length, and maintaining a thickness of 0.4 mm. The print was completed using a 3 ml pneumatic printhead with a 0.2 mm (27G) nozzle. The printed phantom was imaged using the MPI scanner, with slice images obtained by a custom hybrid reconstruction method closely resembling the phantom and demonstrating high imaging quality. The presented work provides a robust foundation for future studies and considerations aimed at advancing the production of MPI phantoms by leveraging the unique capabilities of additive manufacturing. High-resolution phantoms created with tuneable materials can efficiently address the rigorous requirements of various imaging.
Keywords: Hydrogel; 3D Bioprinting; biomedical imaging